The role of kurdish professors' skills and interest in learning in the development of research competences in professors at Kurdish University - Collazos Alarcon, Mercedes Alejandrina (2023)
Professors and institutions of higher education worldwideincreasingly relyon their research skills for success. This aspect calls for the attention of new studies and seasoned policymakers. In light of this, the current article investigates the impact of Kurdish professors' skills and interest in learning on developingtheir research competencies in Kurdish universities. The study also analyzes the moderating effect of research training on the relationship between Kurdish university professors' skills, interest in learning, and the development of research competencies. Using survey questionnaires, the researchers collected primary data from the professors of Kurdish universities. Using smartPLS, the researchers also examined the association between the constructs. The results revealed that Kurdish university professors' skills and interest in learning are positively associated with developingtheir research competencies. The findings also revealed that research training moderates the skills, interest in learning, and development of research competencies among Kurdish university professors. The results provide policymakers with guidelines for establishing policies to improve the research competencies of professors by utilizing their skills, desire to learn, and effective research training